Human Milk Oligosaccharide Composition Differs between Donor Milk and Mother's Own Milk in the NICU. (February 2014) - Marx, Carolin; Bridge, Renee; Wolf, Alison K.; Rich, Wade; Kim, Jae H.; Bode, Lars
Background: Human milk oligosaccharides (HMO) represent the third most abundant component of human breast milk. More than a hundred structurally distinct HMO have been identified, and the HMO composition varies between mothers as well as over the course of lactation. Some newborn infants receive donor milk (DM) when their mother's own milk (MOM) volume is inadequate or unavailable. Objective: This study aimed to compare HMO content between DM and MOM. Methods: We used high performance liquid chromatography analysis of fluorescently labeled HMO to analyze the variation in HMO amount and composition of 31 different batches of DM (each pooled from 3 individual donors) provided by the Mothers' Milk Bank in San Jose, California, and compared it to 26 different MOM samples donated by mothers with infants in our neonatal intensive care unit (NICU). Results: Total HMO amount as well as concentrations of lacto-N-tetraose, lacto-N-neotetraose, lacto-N-fucopentaose 1, and disialyllacto-N-tetraose were significantly lower in DM than in MOM, whereas the concentrations of 3'-sialyllactose and 3-fucosyllactose were significantly higher in DM. Conclusion: Our data show that infants in our NICU who receive DM are likely to ingest HMO at different total amounts and relative composition from what they would receive with their MOM. Recent in vitro and animal studies have started to link individual HMO to infant health and disease. Future studies are needed to assess the importance of a mother-infant match with regard to HMO composition.